Relative age effect and performance in the U16, U18 and U20 European Basketball Championships? - Arrieta, H.; Torres-Unda, J.; Gil, S. M.; Irazusta, J. (Journal of Sports Sciences, 2016)
This study sought to determine the association of relative age and performance of young elite basketball players. The distribution of the birth dates, heights, positions, classification and performance of the male and female participants (n = 2395) of the U16, U18 and U20 European Basketball Championships were analysed. We found an over-representation of players born during the initial months of the year in all groups, with the relative age effect being more evident in players of the U16 and U18 groups, than of the U20 teams, particularly in male squads. Nevertheless, in the U20 championships, those teams that had the oldest players performed the best. In all championships, the oldest participants played more minutes. In addition, relatively older male players scored better in total points and in performance index rating when results were normalised to played time. This effect was not found for female players. Regarding playing position, different distributions of birth dates were observed due to each position`s physical requirements. Thus, basketball coaches and managers should keep these results in mind when they select players because if not, they might subject players who are born towards the end of the year to a negative selection bias.